Application of selected bioinsecticides in management of oryzaephilus surinamensis (coleoptera: Silvaridae) on phoenix dactylifera (date fruits) (2013)
The boinsecticidal potency of three botanicals, namely: Allium sativum (Garlic), Allium cepa (Onion) and Capsicum annum (Red pepper) were tested on Oryzaephilus surinamensis (Saw- toothed grain beetle) infested with Phoenix dactylifera (Date fruits) at exposure periods of three weeks and six weeks in the Department of Zoology, Entomology Laboratory. The boinsecticides used were in powdered and whole forms at three different concentrations of 1.25g, 2.50g and 5.00g. Potency was determined through, fecundity, emergence and mortality rate of the pest under study. At three and six weeks of exposure, mortality between 5.00g concentration of garlic and the control, onion and control were significantly different at p<.05. Application of whole red pepper as boinsecticide was more potent than powdered form, which was significantly different at p<.05. From the study it may be deduced that the tree botanicals have insecticidal potentials which reduced in potency with increase in time and that garlic was more potent than the onion and red pepper.